Numerical simulation of the betatron magnetic field using ELCUT software; MATEC Web of Conferences; Vol. 48 : Space Engineering - Zatonov I. A. Ivan Andreevich (Modern Technologies and Control Methods in the Aviation and Space Industries, 2016)
Title screen